Making bioinformatics training FAIR: the EMBL-EBI training portal - Swan, A. L.; Broadbent, A.; Singh Gaur, P.; Mishra, A.; Gurwitz, K.; Mithani, A.; Morgan, S. L.; Malhotra, G.; Brooksbank, C. (Frontiers in Bioinformatics, 2024)
EMBL-EBI provides a broad range of training in data-driven life sciences. To improve awareness and access to training course listings and to make digital learning materials findable and simple to use, the EMBL-EBI Training website, www.ebi.ac.uk/training, was redesigned and restructured.To provide a framework for the redesign of the website, the FAIR (findable, accessible, interoperable, reusable) principles were applied to both the listings of live training courses and the presentation of on-demand training content. Each of the FAIR principles guided decisions on the choice of technology used to develop the website, including the details provided about training and the way in which training was presented.Since its release the openly accessible website has been accessed by an average of 58,492 users a month. There have also been over 12,000 unique users creating accounts since the functionality was added in March 2022, allowing these users to track their learning and record completion of training.Development of the website was completed using the Agile Scrum project management methodology and a focus on user experience. This framework continues to be used now that the website is live for the maintenance and improvement of the website, as feedback continues to be collected and further ways to make training FAIR are identified. Here, we describe the process of making EMBL-EBI's training FAIR through the development of a new website and our experience of implementing Agile Scrum. Learning outcomes Learning outcomes Learning outcomes Programme Course contents Learning context (e.g. face-to-face, hybrid) EDAM tags EDAM tags EDAM tags